The Iran-China Deal: Challenges for the United States of America in the Middle East - Shakir Hussain (Journal of Peace, Development and Communication, 2022)
The China-Iran Agreement is a twenty-first-century mega initiative that was announced on March 27, 20121 in Tehran, Iran. A 25-year cooperation project has been established by the Chinese Foreign Ministry and the Iranian Foreign Ministry. In the midst of US sanctions against Iran, Iran and China signed a 25-year strategic partnership agreement, which poses the greatest threat to the US and its allies in the Middle East. President Xi Jinping visited Tehran in 2016, when he met with Iran’s Supreme Leader Ali Khamenei and President Hassan Rouhani, and the accord was discussed for the first time. China promised to spend 400 billion in Iran over the next 25 years in exchange for a continuous supply of oil to support its growing economy, as part of a broad economic and security agreement struck on Saturday. The pact has the potential to strengthen China’s influence in the Middle East while also undermining US efforts to isolate Iran. Though, because the US-Iran issue over Iran’s nuclear programme is still unresolved, it is uncertain how much of the agreement would be enforced. China has no intention of taking sides in Iran’s regional confrontation with other countries. Iran, on the other hand, is considered as a useful partner for China in terms of opposing US hegemony or at the very least alarming the US from a global viewpoint.